2012
DOI: 10.1107/s0108270111055120
|View full text |Cite
|
Sign up to set email alerts
|

Two polymorphs and the diethylammonium salt of the barbiturate eldoral

Abstract: Polymorph (Ia) of eldoral [5-ethyl-5-(piperidin-1-yl)barbituric acid or 5-ethyl-5-(piperidin-1-yl)-1,3-diazinane-2,4,6-trione], C(11)H(17)N(3)O(3), displays a hydrogen-bonded layer structure parallel to (100). The piperidine N atom and the barbiturate carbonyl group in the 2-position are utilized in N-H···N and N-H···O=C hydrogen bonds, respectively. The structure of polymorph (Ib) contains pseudosymmetry elements. The two independent molecules of (Ib) are connected via N-H···O=C(4/6-position) and N-H···N(pipe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…This may be achieved by comparing their first molecular environments to one another, as was previously demonstrated for Z ′ > 1 polymorphs of sulfathiazole, 37 2,4,6-trinitrotoluene, 38 carbamazepine, 39 and the barbiturate eldoral. 40 We have carried out such an analysis for polymorph 1-I (CEBGOF 4 ), using the program XPac . 11 It was found that the first environments of molecules 1 and 2 are geometrically very similar with respect to 11 (out of 16) next-neighbor molecules (dissimilarity index 17 x = 2.7).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be achieved by comparing their first molecular environments to one another, as was previously demonstrated for Z ′ > 1 polymorphs of sulfathiazole, 37 2,4,6-trinitrotoluene, 38 carbamazepine, 39 and the barbiturate eldoral. 40 We have carried out such an analysis for polymorph 1-I (CEBGOF 4 ), using the program XPac . 11 It was found that the first environments of molecules 1 and 2 are geometrically very similar with respect to 11 (out of 16) next-neighbor molecules (dissimilarity index 17 x = 2.7).…”
Section: Resultsmentioning
confidence: 99%
“…To gain a better understanding of such a structure, it is useful to establish whether any of the independent molecules are related by a noncrystallographic symmetry transformation. This may be achieved by comparing their first molecular environments to one another, as was previously demonstrated for Z ′ > 1 polymorphs of sulfathiazole, 2,4,6-trinitrotoluene, carbamazepine, and the barbiturate eldoral . We have carried out such an analysis for polymorph 1-I (CEBGOF), using the program XPac .…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, several authors have commented on the occurrence of crystal structures with more than one (Z 0 > 1) independent molecule (Steiner, 2000;Steed, 2003;Desiraju, 2007;Anderson & Steed, 2007;Bernstein, 2011). A better understanding of a given Z 0 > 1 structure may be gained from comparing the geometries of the crystallographically distinct molecular environments of each unique molecule [see, for example, Gelbrich & Hursthouse (2006); Gelbrich et al (2008Gelbrich et al ( , 2013; Gelbrich, Rossi & Griesser (2012)]. In (I), the first environment of molecule A contains 14 molecules, and we have compared the cluster of (1+14) molecules centred on molecule A with the corresponding (1+14) cluster around molecule B using the program XPac (Gelbrich & Hursthouse, 2005).…”
Section: Commentmentioning
confidence: 99%